2016
DOI: 10.2754/avb201685030277
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid profile and nutritional composition of table eggs after supplementation by pumpkin and flaxseed oils

Abstract: The aim of this study was to determine the effect of pumpkin and flaxseed oils on the fatty acid profile and nutrient changes in table eggs. At 38 weeks of age, Lohmann Brown Lite hens were divided into three groups depending up the diet. The birds were housed in individual cages (6 hens per cage) with a space allowance of 943.2 cm 2 per hen, and given diet standard complete feed mixture for laying hens. Hens from experimental groups were fed with complete feed mixtures supplemented by pumpkin (group E1) or fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 18 publications
1
7
1
Order By: Relevance
“…Rowghani et al (2007) stated that rapeseed oil (3% and 5%) increased the percentage of ALA to 3.43% and 6.02%, respectively, and also affected the increase of DHA. Linseed oil also increased Σn-3 PUFA to 4.72% and 6.80% when compared to the control (1.43%), which was also found by Herkel et al (2016). Lewis et al (2000) determined that supplementation of 7% rapeseed oil affected the increase of ALA by × 1.2% to 6.3%, and the increase of DHA × 4.…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Rowghani et al (2007) stated that rapeseed oil (3% and 5%) increased the percentage of ALA to 3.43% and 6.02%, respectively, and also affected the increase of DHA. Linseed oil also increased Σn-3 PUFA to 4.72% and 6.80% when compared to the control (1.43%), which was also found by Herkel et al (2016). Lewis et al (2000) determined that supplementation of 7% rapeseed oil affected the increase of ALA by × 1.2% to 6.3%, and the increase of DHA × 4.…”
Section: Discussionmentioning
confidence: 52%
“…In line with Meluzzi et al (2000), Kralik et al (2008) and Herkel et al (2016), enrichment of eggs with the n-3 PUFA depended on the increased content of n-3 PUFA in the hens' diet, and it was connected with the lowering of n-6 PUFA in egg yolks. According to Simopoulos (2000), LA and ALA are very important as precursors of n-6 PUFA and n-3 PUFA.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…According to Gajčević et al (2009), increasing selenium levels in the feed from 0.2 ppm to 0.4 ppm proportionally increased Se content in the yolk from 573 to 783 ng Se/g, and in albumen from 171 to 345 ng Se/g. Herkel et al (2016) reported that the dietary addition of 3% pumpkin (E1) or linseed (E2) oils increased total n-3 PUFA levels in the eggs from 1.43% (control group) to 4.72% (E1) and 6.80% (E2).…”
Section: Physical-chemical Characteristics Of Designer and Conventionmentioning
confidence: 99%
“…Results of Javad et al (2011) show that egg weight, egg production, fertility and hatchability are significantly affected by diet formulation based on energy, which effects the reproductive performance of hens. Furthermore, according to Herkeľ et al (2016) the addition of oil in to feed of laying hens affects the egg nutrients as well as the quality of yolk. Besides the importance of yolk for embryonic health and hatchability, plays yolk essential role in human nutrition through increasing the energy value and therewith also nutritional value of whole egg.…”
Section: Introductionmentioning
confidence: 99%